CHARACTERISTICS OF PRETERM NEONATES AT THAI NGUYEN NATIONAL HOSPITAL (Vietnam Journal of Community Medicine, 2026)
Objective: To describe the clinical characteristics of preterm neonates treated at Thai Nguyen National Hospital.Methods: A cross-sectional descriptive study was conducted on 110 preterm neonates (2500 g accounted for 63.6%, while 1500–2500 g accounted for 19.1%. The mean body length was 42.5 ± 2.1 cm and mean head circumference was 31.1 ± 2.2 cm. Respiratory rhythm disturbances were observed in 45.5% of cases. Tachycardia occurred in 54.3% and bradycardia in 4.4%. Body temperature ranged from 36.0–37.4°C, equally distributed between 36.0–36.7°C and 36.7–37.4°C (50% each). Delayed primitive reflexes were noted in 18.2%, and 26.4% had hypotonia.Conclusion: Preterm infants in this study were predominantly late preterm, with several postnatal adaptation disorders, including respiratory abnormalities, heart rate instability, and altered muscle tone. These findings highlight the need for close monitoring and appropriate neonatal care tailored to the degree of prematurity.
Keywords: Neonate, preterm, characteristics.